DETERMINANTS OF THE RUSSIAN SHADOW ECONOMY BY CONSIDERING THE SUPPLY CHAIN MANAGEMENT EFFECTS - Mikhaylovna Lizina, Olga; Asymovna Bistyaykina, Dinara; Revaziyevna Ermakova, Eka; Vladimirovna Solovyeva, Tatiana; Vasilyevna Fedonina, Oksana (International Journal of Supply Chain Management, 2019)
The shadow economy in Russia is the most serious problem that destroys the political system and poses a serious threat to the economic security of the country. One of the main solutions to overcome this problem is using the supply chain management strategy in the economy. The aim of this article was to identify the determinants of the shadow economy in Russia and to evaluate their impact on the size of the shadow economy in 2005â?? 2018. To analyze the existing problem, the authors conducted an expert survey and used its results to define the key socioeconomic determinants of the shadow economy. The econometric analysis was performed to identify specific statistically significant factors and their impact on the shadow economy.